Rancang Bangun Sistem Informasi Manajemen Terpadu (SIMANTEP) Online PT. PLN (Persero) Sektor Pembangkitan Tarahan Lampung Dengan Metode Extreme Programming - muludi, Kurnia; Irawati, Anie Rose; candra, bayu ade (Universitas Lampung, 2013)
SMT’s secretariat is one of the PT. PLN (Persero) Power Generation Sector of Tarahan which is responsible fordocument control process. The documents control form start from submission until distribution are still inmanual process, for example, the distributed documents still in the hardcopy. This research creates theIntegrated Management Information System or SIMANTEP Online which is an integrated information systemthat gave online service of documents management at PT. PLN (Persero) Power Generation Sector of TarahanLampung. The information system is made using Extreme Programming (XP), one of Agile DevelopmentMethods. The result of this research is an online information system which is not only accessible in TarahanPLTU’s office area, but also can be accessed by the internet. The SIMANTEP Online also provides conveniencefor the user in terms of documents management and control, start from the submission, validation, anddistribution of documents with online service.